The ROLE OF HRM IN FOSTERING CREATIVITY: AN APPLICATION IN IT ORGANIZATION - Kosovic, Jadranka; Drazeta, Lazar; Djokic, Borivoje (The European Journal of Applied Economics, 2024)
This research paper aims to delve into the significance and role of contemporary Human Resources Management (HRM) practices in not only attracting creative individuals to the organization but also in fostering environments conducive to their work, development, and self-actualization. Understanding how to cultivate creativity at both individual and organizational levels has become crucial for every organization in the Information Technology (IT) industry. These efforts ultimately lead to gaining competitive advantages. With rapid technological advancements and the ensuing competition for talent, the challenge of attracting and retaining high-quality individuals has become increasingly prominent, compelling organizations to seek solutions from HRM. The presented case study in this paper examines the importance of creativity for IT organizations and evaluates the principal components of individual and organizational creativity through a questionnaire comprising 34 questions. The research results highlight HRM practices that contribute significantly. This paper aims to provide insights into theoretical frameworks serving as hypotheses and practical applications of identified practices. Additionally, it encourages HRM practitioners to further explore using the enclosed questionnaire.